2020
DOI: 10.33160/yam.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of C-reactive Protein-to-prealbumin Ratio in Patients with Esophageal Cancer

Abstract: Background The prognostic value of combination of C-reactive protein and prealbumin (CRP/PAlb) in esophageal cancer remains unclear. Methods We enrolled 167 esophageal cancer patients who underwent curative esophagectomy. Univariate and multivariate analyses were performed to determine the prognostic significance of various markers, including CRP-to-albumin (CRP/Alb) ratio, modified Glasgow prognostic score, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and prognostic nutritional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
(43 reference statements)
3
15
0
Order By: Relevance
“…Importantly, the GNRI can be easily calculated from routine hematological data including serum albumin, height, and weight. These readily available parameters can reflect the survival risk in various cancers and have demonstrated utility in elderly patients [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the GNRI can be easily calculated from routine hematological data including serum albumin, height, and weight. These readily available parameters can reflect the survival risk in various cancers and have demonstrated utility in elderly patients [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested that CRP/PAlb was more sensitive to CRP/Alb for cancer prognosis. High CRP/ Alb or CRP/PAlb ratio was significantly associated with bad prognosis [36]. Our results showed that patients who only accepted enteral nutrition had a decreasing trend in the CRP level, but not in the ratio of CRP/Alb and CRP/PAlb.…”
Section: Discussionmentioning
confidence: 46%
“…Besides, PAB is an acute phase reactive protein able to not only effectively evaluate the synthetic ability of the liver, but also reflect the severity of inflammatory response in patients with cardiovascular disease [13] . Matsunaga et al [14] found that the content of PAB in the peripheral blood of patients with unstable angina pectoris is far lower than that in normal people. In this study, the content of hs-CRP and PAB in the peripheral blood of MI patients was detected.…”
Section: Discussionmentioning
confidence: 98%